Supply, installation, testing and commissioning of 415V, 50Hz, TPN+PE sandwich copper type tested busbar trunking (BBT) system etc. for 13 storied Brac University new campus building at holding no. Kha 224, Merul Badda, - Dhaka-1212. , - Brac University (Brac University, 2023)
This agreement made between Brac University and Adex Corporation Ltd. to supply, installation, testing and commissioning of 415V, 50Hz, TPN+PE Sandwich Copper type tested Busbar Trunking (BBT) System etc. for 13 storied Brac University New Campus Building project.